Exploring genetic wealth of tubers for prosperity - Anil, Shirly Raichal; Sheela, M. N.; Devi, A. Asha; Mohan, C.; Radhika, N. Krishna; Asha, K. I. (Indian Horticulture, 2019)
The genetic resources of tuber crops are maintained as field gene banks or ex situ collections, in vitro gene banks, pollen banks, DNA banks and cryobanks. Field gene banks are most commonly followed method of conservation and forms the raw material for crop improvement programmes. Field genebanks are mostly used for conservation of germplasm of clonal crops, often complementary to alternative conservation methods such as in vitro and cryobanks. Field gene bank is the only practical and cost-effective way to conserve the germplasm of clonal crops, especially when resources and skills are limited.